Genome-wide QTL mapping for agronomic traits in the winter wheat cultivar Pindong 34 based on 90K SNP array - Zhang, Liangqi; Luo, Yuqi; Zhong, Xiao; Jia, Guoyun; Chen, Hao; Wang, Yuqi; Zhou, Jianian; Ma, Chunhua; Li, Xin; Huang, Kebing; Yang, Suizhuang; Wang, Jianfeng; et al. (Frontiers in Plant Science, 2024)
Agronomic traits are key components of wheat yield. Exploitation of major underlying quantitative trait loci (QTL) can improve yield potential in wheat breeding. We constructed a recombinant inbred line (RIL) population from Mingxian 169 (MX169) and Pindong 34 (PD34) to detect QTL for grain length (GL), grain width (GW), grain length-width ratio (LWR), plant height (PH), spike length (SL), grain number per spike (GNS), and thousand-grain weight (TGW) across four environments by wheat 90K SNP array. A QTL associated with thousand-grain weight, QTGWpd.swust-6BS, was identified on chromosome 6B, explaining approximately 14.1-16.2% of the phenotypic variation. Additionally, eight QTLs associated with grain length were detected across six chromosomes in four different test environments. These included QGLpd.